Development of short‐range white matter in healthy children and adolescents. Issue 1 (14th October 2017) - Oyefiade, Adeoye A.; Ameis, Stephanie; Lerch, Jason P.; Rockel, Conrad; Szulc, Kamila U.; Scantlebury, Nadia; Decker, Alexandra; Jefferson, Jaleel; Spichak, Simon; Mabbott, Donald J.
Abstract: Neural communication is facilitated by intricate networks of white matter (WM) comprised of both long and short range connections. The maturation of long range WM connections has been extensively characterized, with projection, commissural, and association tracts showing unique trajectories with age. There, however, remains a limited understanding of age‐related changes occurring within short range WM connections, or U‐fibers . These connections are important for local connectivity within lobes and facilitate regional cortical function and greater network economy. Recent studies have explored the maturation of U‐fibers primarily using cross‐sectional study designs. Here, we analyzed diffusion tensor imaging (DTI) data for healthy children and adolescents in both a cross‐sectional ( n = 78; mean age = 13.04 ± 3.27 years) and a primarily longitudinal ( n = 26; mean age = 10.78 ± 2.69 years) cohort. We found significant age‐related differences in fractional anisotropy (FA), mean diffusivity (MD), axial diffusivity (AD) and radial diffusivity (RD) across the frontal, parietal, and temporal lobes of participants within the cross‐sectional cohort. By contrast, we report significant age‐related differences in only FA for participants within the longitudinal cohort. Specifically, larger FA values were observed with age in frontal, parietal, and temporal lobes of the left hemisphere. Our results extend previous findings restricted to long range WM to demonstrate regional changes in the microstructure of short range WM during childhood and adolescence. These changes possibly reflect continued myelination and axonal organization of short range WM with increasing age in more anterior regions of the left hemisphere. Hum Brain Mapp 39:204–217, 2018 . ©2017 Wiley Periodicals, Inc.